Women at war: The crucible of Vietnam. (December 2017) - Pless Kaiser, Anica; Kabat, Daniel H.; Spiro, Avron; Davison, Eve H.; Stellman, Jeanne Mager
Abstract: Relatively little has been written about the military women who served in Vietnam, and there is virtually no literature on deployed civilian women (non-military). We examined the experiences of 1285 American women, military and civilian, who served in Vietnam during the war and responded to a mail survey conducted approximately 25 years later in which they were asked to report and reflect upon their experiences and social and health histories. We compare civilian women, primarily American Red Cross workers, to military women stratified by length of service, describe their demographic characteristics and warzone experiences (including working conditions, exposure to casualties and sexual harassment), and their homecoming following Vietnam. We assess current health and well-being and also compare the sample to age- and temporally-comparable women in the General Social Survey (GSS), with which our survey shared some measures. Short-term (<10 years) military service women (28%) were more likely to report their Vietnam experience as "highly stressful" than were career (>20 years; 12%) and civilian women (13%). Additional differences regarding warzone experiences, homecoming support, and health outcomes were found among groups. All military and civilian women who served in Vietnam were less likely to have married or have had children than women from the general population, χ 2 (8) = 643.72, p < .001. Career military women were happier than women in the general population (48% were "very happy", as compared to 38%). Civilian women who served in Vietnam reported better health than women in the other groups. Regression analyses indicated that long-term physical health was mainly influenced by demographic characteristics, and that mental health and PTSD symptoms were influenced by warzone and homecoming experiences. Overall, this paper provides insight into the experiences of the understudied women who served in Vietnam, and sheds light on subgroup differences within the sample. Highlights: Physical health of women deployed to Vietnam was influenced by warzone experiences. Career military women Vietnam veterans are happier than women in general population. Military and non-military Vietnam service women less likely to marry or have kids. Paper provides insight to mostly unstudied lives of American women of Vietnam War.